Introduction of Disc Material into the Vertebral Canal by Fenestration of Thoracolumbar Discs Following Decompressive Surgery - Harris, Georgina; Freeman, Paul (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective Intervertebral disc extrusion is a common disease affecting chondrodystrophic dogs. It has been reported that fenestration of thoracolumbar intervertebral discs reduces recurrence of disc extrusion and is associated with a low complication rate. One complication reported is iatrogenic introduction of disc material into the canal directly following fenestration. This study aimed to ascertain if, and at what frequency, additional disc material may be introduced into the vertebral canal by fenestration of the affected disc following decompressive surgery.Study Design Twenty-one dogs that underwent hemilaminectomy and disc fenestration for the treatment of thoracolumbar intervertebral disc extrusion had intraoperative assessment of the vertebral canal before and after fenestration. The spinal cord was first decompressed by hemilaminectomy and removal of all visible extruded disc material within the vertebral canal. Once no further material was visible, manual fenestration of the affected disc was performed. The vertebral canal was re-inspected, and the presence or absence of additional material was noted and included in the surgery report.Results Seven dogs showed the presence of new disc material in the vertebral canal post fenestration.This preliminary study shows that additional disc material can be forced into the vertebral canal by fenestration following decompressive surgery, with a frequency of 7/21.Conclusion This illustrates the importance of checking the vertebral canal after fenestration of an extruded intervertebral disc.
Keywords: fenestration; intervertebral; disc; vertebral canal; dog